High-fidelity spin and optical control of single silicon-vacancy centres in silicon carbide - Roland Nagy (Nature Portfolio, 2019)
Point defects in solids have potential applications in quantum technologies, but the mechanisms underlying different defects’ performance are not fully established. Nagy et al. show how the wavefunction symmetry of silicon vacancies in SiC leads to promising optical and spin coherence properties.